Needs analysis of a RELIEVE-based STEM-PjBL e-module for applied science education - Elza Heryensi; Fitri April Yanti; Rendy Wikrama Wardana; Mochamad Lutfi Firdaus (Journal of Environment and Sustainability Education, 2025)
This research aims to analyze the needs and specifications of the Renewable Energy Literacy through the Exploration of Various Natural Materials (RELIEVE) e-module, which is integrated with STEM-PjBL to support applied science learning in universities. This qualitative research involved five lecturers who were selected purposively, with data collected through semi-structured interviews, then transcribed, verified, and analyzed using a thematic approach. The results of the study show three main findings. First, students need learning that is applicable, contextual, interactive, and problem-solving based to develop critical and creative thinking skills. Second, the STEM-PjBL approach is considered appropriate because it is able to integrate science, technology, engineering, and mathematics concepts through contextual projects that increase student learning engagement. Third, the required e-modules must be digital, easily accessible through devices, structured, project-based, and provide authentic assessments to measure high-level thinking skills (HOTS), especially critical and creative thinking skills. These findings confirm that the development of the RELIEVE e-module has the potential to be a strategic pedagogical innovation to strengthen renewable energy literacy and support the sustainable energy transition while contributing to curriculum development and further research on the effectiveness of STEM-PjBL-based learning in higher education.